Report on Mental Disability in Canadian Law - Romero, Luis (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1991)
This is the Canadian Report on the law regulating mental disability in Canadian law, prepared for the XIIIth Congress of the International Academy of Comparative Law held in Montréal in August 1990. The Report has been brought up to date to take account of subsequent changes in the law of the Canadian common law provinces and in the new Civil Code of Québec.In accordance with the instructions given to the national reporters in the above mentioned Congress, the Report first describes at length the law dealing with the civil effects of mental disability, such as the appointment and powers of guardians or curators to administer the property and take important personal decisions for persons with mental disabilities. The Report then discusses the law regulating the involuntary commitment of the mentally disabled to mental health institutions.The Report discerns common trends in the law of Québec and of the Canadian common law provinces. With regard to the appointment of guardians or curators the trend is to move away from judicial declarations of total incapacity, to encourage the self-reliance and cure of the disabled and to grant to the person in charge only those powers absolutely necessary for the protection of the disabled. With regard to the involuntary commitment to mental health institutions, the legislators have been faced with the problem of regulating a decision to deprive a person of her liberty on the basis of a judgment about her mental condition and her future needs, and not on the basis of the commission of a crime or the violation of any law. The legislative solution has been to clarify the standards and criteria which have to be considered before committing a person and to provide more procedural safeguards in the reaching of that decision as well as more opportunities to review and to appeal that decision.